ANALISIS PENILAIAN TINGKAT KESEHATAN BUMN BERDASARKAN ASPEK KEUANGAN PADA PT TELKOM INDONESIA (PERSERO) TBK TAHUN 2016 - 2020 - Annisa Muhamad; Venita Sofiani; Acep Suherman (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to assess the health level of PT Telkom Indonesia (Persero) Tbk in 2016–2020 in the financial aspect based on the Decree of the Minister of BUMN Number: KEP-100/MBU/2002. The assessment based on the financial aspect uses eight indicators, namely return on equity (ROE), return on investment (ROI), cash ratio, current ratio, collection periods, inventory turnover, total asset turnover, and the ratio of equity to total assets. The research method used is a quantitative method with a descriptive type of research. Based on the results of data analysis, it shows that the level of health of PT Telkom Indonesia (Persero) Tbk based on financial aspects during 2016–2020 obtained the title of Healthy (AA) with an interval of 80 < TS <= 95. However, the total score obtained has decreased. In 2016, a total score of 93.57 was obtained. Then, in 2017, it became 92.14. Then in 2018, it became 89.29. In 2019-2020, they obtained the same total score of 86.43.